Antimicrobial and antifungal properties of NiCu-PANI/PVA quaternary nanocomposite synthesized by chemical oxidative polymerization of polyaniline. (March 2022) - Laourari, Ines; Lakhdari, Nadjem; Belgherbi, Ouafia; Medjili, Chahinaz; Berkani, Mohammed; Vasseghian, Yasser; Golzadeh, Nasrin; Lakhdari, Delloula
Abstract: Increasing antimicrobial resistance has led to use of novel technologies such as nanomaterials and nanocomposites that have shown effective antimicrobial and/or antifungal activities against several gram-positive and gram-negative bacteria. There have been limited studies on antimicrobial properties of the combined polymer nanocomposites with transitional bimetallic nanoparticles such as nickel (Ni) and copper (Cu). Thus, the main objective of this study was to synthesis, characterize and investigate the antibacterial and antifungal properties of NiCu-PANI/PVA nanocomposite. The nanocomposite films with different amount of Ni and Cu salts were synthesized by chemical oxidative polymerization of polyaniline using HCl as oxidant and PVA as a stabilizer. Optical, chemical composition, and morphological characteristics as well as thermal stability were evaluated using UV–Visible, FTIR, SEM-EDX, and TGA analyses. Antimicrobial properties were then determined using the disc diffusion assay against gram-negative bacteria (i.e., Escherichia coli ATCC 25922, Klebsiella pneumonia ATCC 700603, Proteus sp., ) and gram-positive bacteria (i.e., Staphylococcus aureus ATCC 2593 ) . Fungal plant pathogens including Aspergillus niger and Fusarium oxysporum f. sp . pisi were also evaluated for determination of antifungal activity of NiCu-PANI/PVA films. Among the synthesized films, Ni65 Cu35 -PANI/PVA showed excellent antibacterial activity against all the bacteria strains examined in this study. The diameters of inhibition zones for Escherichia coli ATCC 25922, Klebsiella pneumoniae ATCC 700603, Proteus sp., and Staphylococcus aureus ATCC 2593 were 23, 23, 17, and 18 mm, respectively indicating good antibacterial activities. Additionally, NiCu-PANI/PVA, particularly the films with higher Cu intake, showed better antifungal activity against Fusarium oxysporum f. sp. pisi . However, NiCu-PANI/PVA was ineffective against Aspergillus niger . Graphical abstract: Image 1 Highlights: Novel NiCu-PANI/PVA quaternary nanocomposite was synthesized. The antibacterial and antifungal properties of novel nanocomposite were investigated. The films with higher copper intake showed better antifungal activity. Novel nanocomposite films are a good candidates to be used as antimicrobial agents.